2014
DOI: 10.1525/jer.2014.9.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Social and Structural Constraints on Disclosure and Informed Consent for HIV Survey Research Involving Female Sex Workers and Their Bar Managers in the Philippines

Abstract: This qualitative study explored the ethical issues of female sex workers’ (FSWs) participation in HIV prevention research. Twenty female bar/spa workers and 10 venue managers in the Philippines underwent individual semi-structured interviews; three community advisory board meetings informed the study design and interpretation of findings. Results: Informed consent was constrained by perceived government coercion and skepticism that research results would translate into community benefits. Disclosure was constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 20 publications
5
32
0
Order By: Relevance
“…Furthermore, she met each participant in the waiting room and shook their hand and said, “I am very happy that you are here to talk with me today.” She also told them at the beginning of the session that they could ask any questions at any time throughout the session. These simple steps helped produce a respectful study environment, which likely positively influenced participants decision to participate in the HIV testing portion of the study as it has among other disadvantaged groups, including female sex workers in India (Reed, Khoshnood, Blankenship, & Fisher, 2014) and the Philippines (Urada & Simmons, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, she met each participant in the waiting room and shook their hand and said, “I am very happy that you are here to talk with me today.” She also told them at the beginning of the session that they could ask any questions at any time throughout the session. These simple steps helped produce a respectful study environment, which likely positively influenced participants decision to participate in the HIV testing portion of the study as it has among other disadvantaged groups, including female sex workers in India (Reed, Khoshnood, Blankenship, & Fisher, 2014) and the Philippines (Urada & Simmons, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Lack of understanding of the privacy protocol of a research study and in some cases lack of confidence in government authorities can cause distrust, perceived intrusiveness, and skepticism for FSWs to participate in research (Urada & Simmons, 2014). These feelings can place social and structural constraints on FSW participation in research studies.…”
mentioning
confidence: 99%
“…The Sunflower Study was unique in providing all participants with HPV testing, treatment for those testing positive, and access to the vaccine for all testing negative. Despite differences in locale, a research focus on HIV versus HPV prevention, and experience participating in sexual health studies, participants’ ethically relevant concerns in many cases paralleled those reported in the Goldenberg et al study and in previous research conducted by RETI fellows (Reed, Khoshnood, Blankenship, & Fisher; 2014; Urada & Simmons, 2014). In relating their experiences, Brown and his colleagues found that FSWs reflected on both the perceived health benefits of participating in the study as well as fears about learning they might test positive for HPV, HIV, or other sexual health diseases.…”
Section: An Overview Of the Special Issue Contributionsmentioning
confidence: 92%